2003
DOI: 10.1002/cpp.352
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a self‐esteem group for people with eating disorders: an uncontrolled study

Abstract: Low self-esteem is widely recognized as a predisposing, precipitating and maintaining factor in the aetiology of eating disorders. This paper examines the effectiveness of a self-esteem group for women with eating disorders, delivered repeatedly over a 20-month period. Fortyone patients began and 33 completed the programme and both preand post-measures. Eight were excluded from the final analysis as they were in concurrent psychological treatment. Outcome was assessed using standardized measures and records of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Improving self-esteem is considered by eating disorder patients and therapists as a core element of treatment (Vanderlinden, Buis, Pieters, & Probst, 2007). Accordingly, the enhancement of self-esteem is already an integral ingredient of many current treatment approaches (Garner, Vitousek, & Pike, 1997;Newns, Bell, & Thomas, 2003;Vitousek, Watson, & Wilson, 1998). However, the findings of this study may suggest that self-esteem should be focused very early in the treatment of AN since weight gain may deprive the patient of an important source of self-esteem.…”
Section: Discussionmentioning
confidence: 86%
“…Improving self-esteem is considered by eating disorder patients and therapists as a core element of treatment (Vanderlinden, Buis, Pieters, & Probst, 2007). Accordingly, the enhancement of self-esteem is already an integral ingredient of many current treatment approaches (Garner, Vitousek, & Pike, 1997;Newns, Bell, & Thomas, 2003;Vitousek, Watson, & Wilson, 1998). However, the findings of this study may suggest that self-esteem should be focused very early in the treatment of AN since weight gain may deprive the patient of an important source of self-esteem.…”
Section: Discussionmentioning
confidence: 86%
“…For people who have an eating disorder, in which low self-esteem is often an underlying cause of their difficulties and maintaining factor (e.g. Newns, Bell, & Thomas, 2003), membership of an eating disorder group which is viewed negatively by others could exacerbate or maintain existing psychological difficulties. These hypotheses are tentative, and it is not suggested that all group members with an eating disorder would be affected in this way, but as stated by Katz et al 'it is important not to overlook the effects of group memberships on individual well-being' (p. 430).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who respond poorly to treatment do indeed have lower levels of self-esteem than those who respond well (Baell & Wertheim, 1992;Fairburn, Kirk, O'Connor, & Anastasiades, 1987;Fairburn, Peveler, Jones, Hope, & Doll, 1993). Likewise, treating self-esteem improves eating disorder symptomatology (Newns, Bell, & Thomas, 2003) and raising self-esteem helps to maintain change following treatment (Beresin, Gordon, & Herzog, 1989;Hsu, Crisp, & Callender, 1992;Peterson & Rosenvinge, 2002;Rorty, Yager, & Rossotto, 1993).…”
Section: Introductionmentioning
confidence: 96%